Effectiveness of the NETES (Niat Engsun Tuntas cEgah Stunting/My Intention to Prevent Stunting Completely) Program to Prevent Stunting - Tutiek Herlina; Nurweningtyas Wisnu; Dian Maheru Robbi; Yuanita Sinar Yuliati; Rahma Anindita (Health Dynamics, 2024)
Background: Stunting was described as a toddler whose height was lower than the standard height for children of the same age, which was a characteristic that indicates repeated and long-term nutritional problems. The negative impact in the long term was decreased cognitive ability and learning achievement, body immunity, and a high risk of diabetes, obesity, heart and blood vessel disease, cancer, stroke, and disability in old age. The prevalence of stunting in Plaosan Subdistrict increased from 2021 by 7.54%, in 2022 by 7.91% and in 2023 by 8.52%. The "NETES" (Niat Engsun Tuntas cEgah Stunting/My Intention to Prevent Stunting Completely) program was one of the stunting management programs in Plaosan Subdistrict, implemented by giving one egg every day for 90 days to children under five at risk of stunting. This research aims to determine effectiveness of the NETES program to prevent stunting. Methods: Research design was ex post facto. The population were all children under five years old who were at risk of stunting, sample size 90 taken by total population. The independent variable was the NETES program and the dependent variable was stunting. The instruments used Endo brand stadiometer and Endo brand infantometer, observation sheets for egg feeding and body height. Analysis by the Wilcoxon Signed Rank test. Results: The results showed median HAZ value before the NETES program was –2.3 and after the NETES program was -1.8.  Z value = 3.8541 and p value = 0.0001162 so it can be concluded that there is a difference HAZ value between before and after the implementation of the NETES program. Conclusions: Giving one egg a day for 90 days is effective to prevent stunting. It is recommended that the implementation of the NETES program can be continued and be applied in other areas.